Modeling the Russian Federation-Asia and the Pacific energy trade - Ehsan Rasoulinezhad; Farhad Taghizadeh-Hesary; Naoyuki Yoshino; Tapan Sarker (Asian Development Bank Institute (ADBI), 2019)
Asia remained the largest market for energy sources in 2018. The Russian Federation has a clear vision to develop its Asian energy projects in order to provide a greater share of Asian energy imports. This paper models Russian Federation-Asia and the Pacific energy trade patterns via the gravity trade theory and GMM panel estimation for quarterly data in the period 2010−2017 for 16 selected Asia and Pacific nations. The results demonstrate that Russian Federation energy exports to Asia and the Pacific follow the Linder hypothesis. Furthermore, the findings reveal that economic growth is a positive influencing factor on the Russian Federation's energy exports to this region. In addition, a depreciation of the national currencies of Asia and Pacific nations against the Russian ruble will accelerate the latter's energy export volume. To improve energy security in this region, we recommend policies such as the development of an energy trading hub in Asia, increased regional pricing power, and energy import diversification and reduced distance between the Russian Federation (exporter) and Asia and the Pacific (importers).
Keywords: Q37; R11; F14; 330; Asia and the Pacific; energy trade; energy security; gravity trade modeling; Russian Federation